Delayed right coronary ostial obstruction after J-valve deployment in transcatheter aortic valve implantation: A case report - Xu, Zhao (World J Clin Cases, 2020)
BACKGROUND: Aortic stenosis is the most common valve disease in adults. Transcatheter aortic valve implantation (TAVI) is being increasingly applied for intermediate- to low-risk patients. Here, we describe an uncommon complication of delayed right coronary obstruction in a transapical TAVI case. CASE SUMMARY: A 73-year-old woman with a EuroSCORE II of 1.21% underwent transapical TAVI because of severe aortic stenosis. The surgical procedure was uneventful. However, during routine monitoring after valve placement, the patient had a sudden onset of slow heart rate, the systolic blood pressure dropped sharply from 115 to 60 mmHg, and the central venous pressure abruptly increased from 10 to 33 cmH(2)O. The patient had a poor response to vasoactive agents. Transesophageal echocardiography revealed poor myocardial contractility, and electrocardiography showed a significant depression of ST-segment. Another angiography was performed immediately, which suggested complete obstruction of the right coronary artery. An emergency protocol was initiated. Cardiopulmonary bypass was established immediately. An aortic biological valve replacement under cardiopulmonary bypass was performed. CONCLUSION: Perioperative monitoring, early recognition, and diagnosis of obstruction of coronary arteries in TAVI are important. Transesophageal echocardiography is a useful diagnostic and monitoring tool in this situation. Emergency protocols should be established during TAVI.